The Use of Short Video Clips to Improve Students’ Comprehension in Learning Simple Present Tense - Najwa Safira; Nuzulul Isna (Universitas Islam Negeri Palopo, 2025)
This research investigates the effectiveness of using short video clips to enhance students’ comprehension of the Simple Present Tense in English language learning. The study employed a pre-experimental design with a one-group pre-test and post- test model, involving 31 seventh-grade students at SMP Negeri 1 Kuala Batee. Data collection was conducted through multiple-choice tests administered before and after the treatment. The analysis showed a significant improvement in students’ understanding, with the average pre-test score rising from 43.39 to 74.19 in the post- test. A paired sample t-test revealed a statistically significant difference (Sig. 2-tailed = 0.000), confirming the effectiveness of short video clips in improving grammatical comprehension. These findings suggest that incorporating engaging and context-rich audiovisual materials can significantly support grammar instruction in English as a Foreign Language (EFL) setting. However, limitations such as the small sample size call for further research involving broader and more diverse populations to generalize the results. Additionally, combining short video clips with other interactive teaching strategies is recommended to maximize learning outcomes.